Pengaruh Mesin Cutting Otomatis Berbasis Internet of Thing (IoT) terhadap Efisiensi dan Produktivitas Pekerja Pada Mesin Building Tire di PT. ABC - latifah ahmad, Tita; Puspa Murni, Indah; Triya Nur Adibah, Anisa; Andre (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2024)
Several studies have been carried out to apply Internet of Things (IoT) technology in the environment manufacturing to increase efficiency and productivity. However, no comprehensive report is available about IoT methods and technology applied in automatic cutting machines in the Building Tire process. A systematic literature review was conducted to fill this gap by adopting an approach systematic through literature searches from various databases (Google Scholar, ScienceDirect, IEEE Explore, and MDPI). This review analyzes the methods and technologies that support deep IoT implementation manufacturing environment, including REST API integration with ERP, Vision-Based Data Reader, algorithms decision tree, as well as a comprehensive integration approach in Smart Factory through Horizontal, Vertical Integration Integration, and End-to-End Integration. The literature review found various supporting technologies such as smart sensors, cloud computing, big data analytics, edge computing, and digital twin platforms play a role important in IoT implementation. It was found that the implementation of IoT allows monitoring the condition of machines in real-time, fast data analysis, and significantly increase production efficiency. Besides that, Algorithms such as decision trees are able to classify real and fake data with a high level of accuracy high, supports online validation and improves system reliability. Due to the huge potential in IoT, methods and the technologies examined in this literature form a solid foundation for IoT development in manufacturing environment, facilitating adaptation to the Industrial 4.0 era by creating adaptive systems, efficient, and responsive to changing market needs.